Assessing The Relationship of Loyverse Pos System Utilization to Financial Reporting Quality in Retail Businesses - Dagohoy, Nicolle; del Prado, Megan; Belotindos, Jerico; Alfanta, Mylene (Disclosure: Journal of Accounting and Finance, 2026)
The increasing integration of digital technologies in retail operations has reshaped financial management practices, highlighting the need for reliable point-of-sale (POS) systems to enhance reporting accuracy. The participants were retail businesses specifically aiming for the pharmacies and the convenience stores located within Pagadian City, Zamboanga del Sur and the representatives were selected by employing an inclusive sampling strategy to determine the respondents through purposive sampling based on a specific criterion. Survey questionnaires adapted from the study of Zamzami et al. (2024) and Zainal et al. (2024) were administered to 43 respondents, which aimed to assess two variables: level of utilization of Loyverse POS system - trialability, technology context, organizational context, environmental context, adoption and integration, relative advantage, compatibility, and complexity; and the level of improvement in financial reporting quality - relevance, faithful representation, comparability, verifiability, understandability, and timeliness. Moreover, a correlational research design was used as the research design, wherein findings revealed that the Loyverse POS system was highly utilized overall and the system significantly improved financial reporting quality across all indicators, leading to a Highly Positive Correlation between the two variables. Based on these findings, the study recommends standardized operating procedures, capacity-building initiatives, and curriculum integration to strengthen system adoption, reduce complexity, and further improve reporting reliability in the retail sector.